Improvement of fertility in repeat breeder dairy cattle by embryo transfer following artificial insemination: possibility of interferon tau replenishment effect - Hikari YAGINUMA; Natsumi FUNESHIMA; Nao TANIKAWA; Motoharu MIYAMURA; Hideki TSUCHIYA; Tatsuo NOGUCHI; Hisataka IWATA; Takehito KUWAYAMA; Koumei SHIRASUNA; Seizo HAMANO (The Society for Reproduction and Development, 2019)
Repeat breeder cattle do not become pregnant until after three or more breeding attempts; this represents a critical reproductive disorder. Embryo transfer (ET) following artificial insemination (AI) in repeat breeder cattle reportedly improves pregnancy rate, leading to speculation that interferon tau (IFNT) is associated with this phenomenon. However, the reason why the conception rate improves remains unknown. We investigated the effect of ET following AI on repeat breeder cattle in field tests, and determined whether adding an embryo affects the maternal immune cells detected by interferon-stimulated genes (ISGs), marker genes of IFN response. In total, 1122 repeat breeder cattle were implanted with in vitro fertilization (IVF) embryos after previous AI. ET following AI resulted in pregnancy rates of 46.9% in repeat breeder dairy cattle. In basic in vivo tests, to investigate the effect of adding embryos, ISGs mRNA expression levels were significantly higher in the AI + ET group than in the AI + sham group (transfer of only embryonic cryopreservation solution). Then, we examined the effect of cultured conditioned media (CM) of IVF embryos on splenic immune cells and Madin-Darby bovine kidney (MDBK) cells with stably introduced ISG15 promoter-reporter constructs. These cells exhibited a specific increase in ISG15 mRNA expression and promoter activity when treated with the CM of IVF embryos, suggesting that IVF embryos have the potential to produce and release IFNT. In conclusion, ET following AI is beneficial for improving conception in repeat breeder cattle. Added embryos may produce and secrete IFNT, resulting in the increased expression of ISGs.